Larval Habitat Associations with Human Land Uses, Roads, Rivers, and Land Cover for Anopheles albimanus, A. pseudopunctipennis, and A. punctimacula (Diptera: Culicidae) in Coastal and Highland Ecuador - Pinault, Lauren L.; Hunter, Fiona F. (Frontiers in Physiology, 2012)
Larval habitat for three highland Anopheles species: Anopheles albimanus Wiedemann, Anopheles pseudopunctipennis Theobald, and Anopheles punctimacula Dyar & Knab was related to human land uses, rivers, roads, and remotely sensed land cover classifications in the western Ecuadorian Andes. Of the five commonly-observed human land uses, cattle pasture (n=30) provided potentially suitable habitat for An. punctimacula and An. albimanus in less than 14% of sites, and was related in a Principal Components Analysis (PCA) to the presence of macrophyte vegetation, greater surface area, clarity and algae cover. Empty lots (n=30) were related in the PCA to incident sunlight and provided potential habitat for An. pseudopunctipennis and An. albimanus in less than 14% of sites. The other land uses surveyed (banana, sugarcane and mixed tree plantations; n=28, 21, 25, respectively) provided very little standing water that could potentially be used for larval habitat. River edges and eddies (n=41) were associated with greater clarity, depth, temperature and algae cover, which provide potentially suitable habitat for An. albimanus in 58% of sites and An. pseudopunctipennis in 29% of sites. Road-associated water bodies (n=38) provided potential habitat for An. punctimacula in 44% of sites and An. albimanus in 26% of sites surveyed. Species collection localities were compared to land cover classifications using Geographic Information Systems software. All three mosquito species were associated more often with the category "closed/open broadleaved evergreen and/or semi-deciduous forests" than expected (P ≤ 0.01 in all cases), given such a habitat's abundance. This study provides evidence that specific human land uses create habitat for potential malaria vectors in highland regions of the Andes.